Pengaruh Field Trip terhadap Kemampuan Literasi Sains dan Sikap terhadap Sains Siswa SMA pada Materi Ekosistem - Dinata, Anita Nurlela; Adisendjaja, Yusuf Hilmi; Amprasto, Amprasto (Assimilation: Indonesian Journal of Biology Education, 2018)
The aim of this research is to know the influence of field trip on scientific literacy and attitude towards science of senior high school students before and after the field trip implemetation in ecosystem learning. The research was conducted in SMAN I Pangalengan. The method which was used in this research is Quasi Experimental with Nonequivalent Control Group Design as the design. The result shows that there are significant difference in scientific literacy between the control class where discussion was applied and the experimental class where field trip was applied, with t = 0.003 and Î± = 0.05. The result also shows that there is a significant attitude between the control and experimental class, with t = 0.003 and Î± = 0.05. Those results show that field trip gives significant effect on high school student's scientific literacy and attitude towards science in ecosystem concept.